Relationship of PROP (6-n-propylthiouracil) taster status of Filipino women with their intensity and hedonic responses to vegetables - Paredes, Karla Marie B.
ABSTRACT The study aimed to determine the relationship of PROP (6-n-propylthiouracil) taster status of Filipino women with their intensity perception and hedonic responses to selected vegetables. . Suprathreshold scaling, using increasing concentrations of PROP and NaCl solutions rated in the Labeled Magnitude Scale (LMS), determined the PROP taster status of the selected participants. Vegetable samples (cabbage, lettuce, petchay, kangkong, ampalaya) were evaluated using the 9-point hedonic scale for hedonic response (bitter taste, flavor, and overall acceptability) and LMS for bitter intensity perception. The Filipino women population in this study was found to be 7.27% nontasters, 34.55% medium tasters and 58.18% supertasters. Results revealed that bitter taste intensity perception was not related to PROP taster status, except for ampalaya, which was also rated as having the highest bitter intensity by all taster classifications. The latter's bitter taste intensity perception and acceptance were correlated (p<0.05) with PROP sensitivity. Spearman's rank correlations between significant (p<0.05) bitter taste intensity and acceptance parameters of vegetables showed that an increase in bitter taste intensity would decrease acceptance scores for PROP tasters, and would increase acceptance scores for nontasters.